UPAYA PENEGAKAN HUKUM TERHADAP TINDAK PIDANA KORUPSI DI KOTA SAMARINDA - La Sina (Faculty of Law, Universitas Diponegoro, 2015)
Speaking of corruption is being aggressively reviled by various circles of society , people no longer trust law enforcement corruption . With a variety of reasons escape corruption charges. Is this making people more amused components against corruption . Born as a result of the impact of corruption is very dangerous , one of which the decline of the national economy . Anti-corruption efforts solely through the prosecution of corruption , whereas the present moment awareness need everyone to obey the law of corruption .The perpetrators of corruption in Samarinda always hide behind the policies and provisions contained in the legislation governing the authority of an agency or official , so as though everything is a discretionary authority .This type of research used in this paper is an empirical legal research methods with qualitative approach to analyze the data that refers to the rules and regulations perudang . So as to obtain an overview of the impact of corruption in public life , analyze and formulate on law enforcement corruption , and to analyze the factors that affect the law enforcement corruption in the city of Samarinda